A Comparative Study Of Stomatal Characteristics of The Nine Pandanus Species From Nias Island, North Sumatra Province, Indonesia - Zebua, Helmin Parida; Pasaribu, Nursahara; Siregar, Etti Sartina (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2024)
AbstractThe identification of Pandanus species generally relies on morphological characteristics and requires confirmation from other identification features, such as stomata. A comparative study of stomatal characteristics among nine Pandan species originally from Nias Island, namely Pandanus atrocarpus, P. auranticus, P. labyrinthicus, P. militaris, P. odoratissimus, P. penangensis, P. tectorius, and P. utilis has been investigated. Anomocytic stomata without papillae on subsidiary cells were observed on both leaf surfaces, with significant interspecific differences in adaxial and abaxial stomatal frequencies. Pandanus tectorius exhibited the highest adaxial (30.71 ± 0.81) and abaxial (1.87 ± 0.12) stomatal frequencies. Pandanus labyrinthicus showed the highest stomatal index (adaxial 16.61 ± 2.51, abaxial 0.87 ± 0.11), while P. penangensis had the largest stomatal size (137.54 ± 6.66 µm). Overall, the stomatal parameters, including frequency, index, and size, were higher on the adaxial surface than the abaxial surface, emphasizing interspecific variations. These findings contribute valuable supportive data for the botanical systematics of Pandanus spp. in the region, enhancing our understanding of morphological characteristics crucial for species identification.AbstrakIdentifikasi jenis dari Pandanus cenderung menggunakan ciri morfologi dan memerlukan konfirmasi dari karakter lainnya, salah satunya stomata. Studi perbandingan stomata di antara sembilan spesies Pandan di Pulau Nias, Sumatera Utara telah dilakukan, yaitu Pandanus atrocarpus, P. auranticus, P. labirinthicus, P. militaris, P. odoratissimus, P. penangensis, P. tectorius, dan P. utilis. Hasil penelitian menunjukkan bahwa keseluruhan jenis Pandanus memiliki tipe stomata berupa anomositik pada kedua permukaan daun atau amfistomatous tanpa adanya papilosa pada sel tambahan. Frekuensi stomata adaksial dan abaksial memiliki perbedaan yang nyata secara statistik lintas jenis. Frekuensi stomata tertinggi pada daun adaksial/abaksial diamati berturut-turut dari P. tectorius (30,71 ± 0,81) dan P. tectorius (1,87 ± 0,12). Indeks stomata daun tertinggi diamati berturut-turut berasal dari P. labirinthicus (16,61 ± 2,51) untuk adaxial dan P. labirinthicus (0,87 ± 0,11) untuk abaxial. Ukuran stomata terbesar diamati berturut-turut berasal dari P. penangensis (137,54 ± 6,66 µm) dan P. odoratissimus (64,56 ± 3,96 µm). Secara umum, tipe stomata pada semua jenis adalah anomositik tanpa adanya papila pada sel penjaga. Parameter stomata lainnya, yaitu frekuensi, indeks, dan ukuran pada bagian adaksial cenderung lebih tinggi dibandingkan permukaan abaksial dengan variasi nilai secara interspesifik.